Flipped Learning for Teaching Ukrainian IT Students - Yalova, Kateryna; Yashyna, Ksenia; Sorokina, Liudmyla (International Journal of Research in E-learning, 2020)
The paper is devoted to utilisation of flipped learning for improving educational quality for IT students. The article discusses the advantages and disadvantages of flipped learning, the obstacles for its adoption are also described. The modification of educational functions, roles, actions, and interconnections of the participants during implementation of flipped learning is shown. Flipped learning implementation algorithm is proposed for a university discipline. Uniform architecture for flipped course which consists of face-to-face and online parts is provided. Forms and requirements for e-content are described. Approaches and technologies for implementing the online part of flipped learning are also discussed. Innovative educational technologies which may be useful at the stages of meaning realisation and knowledge reflection as well as for creating professional students’ skills are proposed. The proposed solutions are uniform and formed by generalisation of the knowledge about the data domain, they can be utilised at Ukrainian universities.